The influence of board characteristics on earnings quality in Chinese listed family companies - Yang, Yifan (2020)
The research explores how the board characteristics in Chinese family enterprises influence earnings quality. According to the relevant literature and theories of the family enterprises’ board characteristics and earnings quality, the study selects 168 listed family businesses in the main board of Shanghai and Shenzhen stock exchanges from 2015 to 2018 as empirical research samples. The modified Jones model is applied to calculate the discretionary accruals as the measurement for earnings quality. The board size, board duality, the proportion of family members on the board, the board independence, the board meeting frequency are considered as board characteristics. As shown in the empirical results, a high proportion of family members on the board is significantly related to higher earnings quality, and more board meetings will improve the earnings quality. Besides, the larger ratio of independent directors is associated with a higher quality of earnings. Moreover, the board size is found significantly negative with earnings quality. However, there exist no correlations between board duality and earnings quality.